Desenvolvimento de botões florais da pinheira em função da adubação nitrogenada e potássica - Souza, Ivan Vilas Bôas; José, Abel Rebouças São; Da Silva, José Carlson Gusmão; Bomfim, Marinês Pereira [UNESP]; De Jesus, Jecilene Silva (FapUNIFESP (SciELO), 2016)
The custard apple tree (Annona squamosa L.), has increased in cultivation due to good prices in the national market. However, there are few studies regarding the fruit’s nutrition. The aim of this study was to verify the influence of N and K levels in developing the flower buds in two growing cycles, corresponding to the time of high temperatures (spring-summer) and another milder season (autumn-winter). The experiment was conducted in a rural property located in the municipality of Anagé, Bahia, installed in a randomised complete block design with 3 blocks, arranged in a factorial 4 x 4, obtained by the combination of the following levels of N (0, 16.875, 33.750 and 67.500 g plant-1) in the form of urea and K (0, 22.5, 45.0 and 90.0 g plant-1) in the form of potassium chloride, applied every fifteen days (every fortnight/every two weeks). It was evaluated the vigor of floral buds, measured by determining its weight and the length of them. At the end of the study it was concluded that the vigor of the floral buds tended to increase with elevated levels of nitrogen in the coldest period of the year (dry season with low in temperature). In the spring-summer period (rainy season and high temperature) the vigor of the flower buds was reduced as they increased the doses of N. Potassium did not affect the vigor of the flower buds in these considered periods. There was no interaction between N and K levels for the vigor of the flower buds.
The development of custard apple flower bud under nitrogen and potassium nutrition
Keywords: Annona squamosa L; Annonaceae; Floral quality; Growth; Nutrition